(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Post-operative pain management in abdominal surgery remains a challenge, with the need to optimise analgesic efficacy while minimising opioid consumption and adverse effects. Two regional anaesthesia techniques the Erector Spinae Plane Block (ESPB) and the Transversus Abdominis Plane Block (TAP block) have been increasingly used for abdominal wall and visceral analgesia. Aim: To compare the analgesic efficacy of ESPB versus TAP block in adult patients undergoing elective abdominal surgeries under general anaesthesia, with respect to postoperative pain scores, 24-hour opioid consumption, time to first rescue analgesic, incidence of nausea/vomiting, and duration of hospital stay. Methods: In this prospective observational study a profile of 120 adult patients (ASA I&II) scheduled for elective midline or lateral abdominal surgeries were randomly assigned to receive either bilateral ultrasound-guided ESP block (n = 60) or bilateral ultrasound-guided TAP block (n = 60) after induction of general anaesthesia. Blocks were performed using 20 mL of 0.375 % bupivacaine per side with standardised intraoperative and postoperative analgesic protocols. Primary outcomes were postoperative visual analogue scale (VAS) pain scores at rest and on movement at 6, 12 and 24 hours, and cumulative 24-hour morphine equivalent consumption. Secondary outcomes included time to first rescue analgesic, incidence of postoperative nausea and vomiting (PONV), patient satisfaction (numeric rating scale), and length of hospital stay. Results: Patients in the ESPB group had significantly lower mean VAS scores at 6 h (3.2 ± 1.1 vs 4.6 ± 1.4, p < 0.001), at 12 h (3.8 ± 1.3 vs 5.1 ± 1.5, p < 0.001) and at 24 h (4.1 ± 1.4 vs 5.6 ± 1.6, p < 0.001) compared with the TAP block group. The 24-hour morphine equivalent consumption was 18.3 ± 5.2 mg in the ESPB group versus 24.7 ± 6.8 mg in the TAP group (p < 0.001). Time to first rescue analgesic was longer in the ESPB group (9.8 ± 2.4 h vs 7.1 ± 1.9 h, p < 0.001). The incidence of PONV was lower in the ESPB group (13.3 %) compared to the TAP group (26.7 %), p = 0.042. There was no significant difference in length of hospital stay (ESPB: 2.9 ± 0.5 days vs TAP: 3.0 ± 0.6 days, p = 0.18). Patient satisfaction scores were higher in the ESPB group (8.6 ± 0.7) than in the TAP group (7.9 ± 0.9), p = 0.003. Conclusion: In adult patients undergoing elective abdominal surgery, the erector spinae plane block provided superior analgesic efficacy compared to the transversus abdominis plane block, as evidenced by lower pain scores, reduced opioid consumption, longer analgesia duration and lower incidence of PONV. The findings support ESPB as a favourable regional analgesic technique for abdominal procedures, though further multicentre trials are needed to define optimal volumes, concentrations and injection levels.